Writing Error: Exploring the Language Interference in EFL Context - Aisyah Nur Cahyani; Irfan Wahyudi; Farrah Maulida Nadia; Nadiatur Ramaniyah; Ning Ayu Dinanti; Kinanti Dyah Lestari; Richa Dian Yulianti; Durratul Hikmah (Universitas Nurul Jadid, 2023)
Al-Mashduqiah Plus Junior High School is one of the boarding school that develops foreign language skills as an attempt to prepare young people to be able to compete in the global world. In fact, the language learners (students) still often mix the structure of their first language into English to write. Therefore, this study aimed to identify the language interference in the students’ English writing assignment, and what factors behind them. The research used descriptive qualitative. The results showed that the form of interference in Al- Mashduqiah Plus Junior High School is morphological and syntactical structure. Besides, these interferences are caused by several factors; they are structural and non-structural factors. The structural factors include the difference of linguistics systems in native language and the targeted language. The non-structural factors include the learners’ bilingualism, language loyalty, the inadequate vocabulary of learners’ language, and the habits of using mother tongue language. This research is expected to provide information to students, teachers, and researchers so that they can find learning innovations that can improve the quality of foreign language skills.